Etyka : poglady i problemy - Vardy, Peter; Grosch, Paul. (Poznan : Zysk i S-ka, 1995)
Polish translation of "The puzzle of ethics". A study of applying ethics to our lives.
Includes bibliographical references (p. [219]-221).
Keywords: Ethics